Nasal carriage of Methicillin Resistant Staphylococcus aureus among health care workers in a tertiary care hospital - Krishnakumar, Sharanya; Krishnasamy, Lakshmi; Krishnagopal, Vinod; Saikumar, Chitralekha (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: Hospital acquired infections especially with methicillin resistant Staphylococcus aureus (MRSA) is an important cause of morbidity and mortality. Staphylococcus aureus remains as a significant and potential pathogen because of its severity and increased frequency in causing a wide array of infections. The most common infections caused by S. aureus include skin and soft tissue, musculoskeletal system, respiratory system, central nervous system, endovascular system &genitourinary system. It has become one of the leading causes of hospital acquired infections and are very difficult to treat because of increase in resistance to antimicrobial drugs. Aim and objectives: This study aims to screen for nasal carriage of Staphylococcus species, Methicillin Resistant Staphylococcus aureus (MRSA) and Methicillin Sensitive Staphylococcus aureus (MSSA) among the health care workers as they are potentially endangered target groups in a health care setting. Materials and Methods: The study was carried out in a tertiary care hospital for a period of 6 months from June 2018 to December 2018. Nasal swab samples were obtained from a total of 120 health care workers. Culture and sensitivity was performed by standard microbiological methods. Methicillin resistance was tested by using Cefoxitin disc (30μg) by Kirby-Bauer disk diffusion method on Mueller Hinton Agar. Results: Out of the 120 samples, 86 (72%) samples were bacterial culture positive and 34(28%) samples were culture negative. Among the 86 clinical isolates, 38 (31.6%) were of Staphylococcus aureus, 26 (21.6%) were of Coagulase negative Staphylococcus aureus (CONS) and 22 (18.3%) samples were of bacteria other than Staphylococci. Conclusion: A higher rate of nasal carriage of MRSA was observed among the health care workers. Henceforth, routine screening of MRSA among the hospital staffs is recommended.